Fostering (supra-)regional cooperation through LEADER/CLLD - Lynn-Livia Fynn; Kim Pollermann (ZBW - Leibniz Information Centre for Economics, 2023)
Community-led local development (CLLD), initiated as LEADER in 1991, is a bottom-up-oriented, participatory approach driven by cooperation between local actors in rural areas. It forms part of regional development programmes (RDPs), which are the basis of funding in rural areas in the EU. Through LEADER/CLLD, budgets are allocated to LEADER regions on the local level to support the implementation of projects in line with so-calledlocal development strategies (LDS), which state the distinct objectives for local development in each region. This contribution focusses on one of the LEADER features, namely "LEADER cooperation", which explicitly supports cooperation between rural communities from two or more different regions through joint projects. The two main types of cooperation are 1. inter-territorial cooperation between two or more LAGs or comparable groups within a Member State and 2. transnational cooperation between two or more LAGs or comparable groups from different Member States. In our contribution, we present and discuss the state of implementation (experiences with different types, topics) as well as administrative aspects and outcomes of cooperation projects based on data from the evaluation of LEADER in four German federal states . In a first analysis of results, the larger time investment required in supraregional cooperation and different project selection criteria are identified as common challenges faced during the planning and management of LEADER cooperation projects while knowledge gain is widely seen as an added benefit.
Conference: 61st ERSA Congress: Disparities in a Digitalising (Post-Covid) world – Networks, Entrepreneurship and Regional Development. Hybrid conference/Pécs, Hungary 22nd – 26th August, 2022
Keywords: R58; 330; LEADER; cooperation project; rural partnership; Germany